2012
DOI: 10.5402/2012/126720
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effects of Low-Level Laser Therapy on the Thyroid Vascularization of Patients with Autoimmune Hypothyroidism by Color Doppler Ultrasound

Abstract: Background. Chronic autoimmune thyroiditis (CAT) frequently alters thyroid vascularization, likely as a result of the autoimmune process. Objective. To evaluate the effects of low-level laser therapy (LLLT) on the thyroid vascularization of patients with hypothyroidism induced by CAT using color Doppler ultrasound parameters. Methods. In this randomized clinical trial, 43 patients who underwent levothyroxine replacement for CAT-induced hypothyroidism were randomly assigned to receive either 10 sessions of LLLT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…The US performed 30 days RCT postintervention showed that the proportion of patients with a normal TVP was higher in the L group than in the P group [ 7 ], but in the present study, this proportion did not differ significantly. This finding indicates that the effects of LLLT on the improvement of TVP are also transient.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The US performed 30 days RCT postintervention showed that the proportion of patients with a normal TVP was higher in the L group than in the P group [ 7 ], but in the present study, this proportion did not differ significantly. This finding indicates that the effects of LLLT on the improvement of TVP are also transient.…”
Section: Discussioncontrasting
confidence: 84%
“…The RCT showed evidence that LLLT promoted the following: (a) an improvement in thyroid function, as indicated by the reduction in the dose of LT4 used to treat hypothyroidism; (b) a reduction in serum anti-TPO concentrations; and (c) improvement in the echogenicity, volume, and thyroid vascularization pattern in CDU [ 6 , 7 ]. Such results suggest that LLLT may be an interesting alternative for the treatment of CAT-induced hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to improved thyroid function they found reduced autoimmunity evidenced by lower thyroid peroxidase antibodies (TPOAb), and thyroglobulin antibodies (TgAb). A third study [ 91 ] used color Doppler ultrasound to show improved normal vascualrization in the thyroid parenchyma. Finally [ 92 ] they showed a statistically significant increase in serum TGF-β1 levels 30 days post-intervention in the PBM group, thus confirming the anti-inflammatory effect.…”
Section: Clinical Applications Of Pbm For Inflammationmentioning
confidence: 99%
“…The beneficial effects of red and infrared light in the treatment of inflammation have been well known since the time of Niels Finsen, who received the Nobel Prize in 1903 for his demonstration that a human autoimmune disease, lupus vulgaris , could be successfully treated and cured by application of visible light [ 2 ]. In subsequent years, illumination of patients with red or infrared light, known as Photobiomodulation therapy (PBM), was proven clinically effective against a variety of human diseases including Achilles tendinopathy [ 3 ], Alopecia Areata [ 4–6 ], psoriasis [ 7–9 ], thyroiditis [ 10 , 41 ], and arthritis [ 11–13 ]. A unifying feature of all of these conditions is that they involve excessive inflammation [ 3 , 5 , 9 , 14 ].…”
Section: Introductionmentioning
confidence: 99%